Contested Access in the Failing Urban Culinary Tourism Planning: A Case of Bogor, Indonesia - Agustina Multi Purnomo (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
This study explores the role of urban tourism planning at the national and regional levels in developing Indonesia’s culinary tourism destinations. Culinary destination tourism planning in Indonesia is under‐researched. This study aims to fill the gaps. Using the spatial triad analysis, this study explores the interrelatedness between the conceived-perceived-lived government planning activities in shaping culinary tourism destinations. Bogor City case was chosen because it has a higher culinary growth rate than other nearby cities. Bogor City analyzed in regional and national context. Based on the observations and the document studies, including text, promotion, publication, and document analysis, the research found that government culinary tourism planning has failed to develop culinary tourist destinations and attractions. The problem lies in the inconsistency between equivalent policies and the discontinuity between policy and implementation. The research findings indicate the governments lack of understanding of the subject matter and planning mechanisms. The culinary tourism planning activities have also created a classical contest of capital power. This research finding suggests the need for a better understanding of culinary tourism attractions and destinations and better planning mechanisms.